TRANSLATION OF GERMAN LANGUAGE PARTICIPAL CONSTRUCTIONS INTO UKRAINIAN BASED ON OFFICIAL AND BUSINESS DISCOURSE TEXTS - Иваница, Иванна (SWorldJournal, 2020)
The article analyzes the frequency of use of German language participal constructions in the texts of the official and business discourse of the German language and looks into the peculiarities of the translation of these constructions into Ukrainian. Th